An Analysis of Parasocial Interaction Patterns between Travel Micro-influencers and Viewers on YouTube - Nadia Zahara; Tuti Bahfiarti; Muhammad Farid (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Advances in communication technology and social media have significantly transformed the travel industry, particularly through the emergence of travel influencers on a variety of social media platforms. Specifically, this study aims to identify the patterns of parasocial interactions between travel micro-influencers and their viewers on YouTube. Parasocial interaction is defined as one-sided interaction with media personalities during media exposure. The data were collected from YouTube’s travel videos about Yogyakarta as one of the most visited cities in Indonesia, which were produced by five Indonesian travel micro-influencers who have followers under 100.000. Using qualitative content analysis, the video content and comments were coded and examined. The findings reveal that micro-influencers create parasocial interaction patterns through several key aspects, including physical attractiveness, interpersonal communication skills, information sharing, destination appeal, production techniques, and confirmation. Meanwhile, the audience engages in a parasocial manner through expressions of admiration and appreciation, active involvement, interaction, emotional bonds, inspiration, and practical influence. Although the established interaction is primarily one-way, some of these interactions are reciprocal, such as when the influencers reply to the viewer's comments. This pattern of interaction demonstrates that YouTube serves as a platform for creating and maintaining parasocial relationships between viewers and influencers in addition to operating as a platform for content distribution.